(untitled) (Journal of Plant Disease Sciences, 2025)
Chilli is a vital spice and vegetable crop that suffers significant yield losses due to damping-off disease, primarily caused by Pythium aphanidermatum. The present study was undertaken to evaluate the efficacy of selected botanical extracts and microbial bioagents against this pathogen under in vitro conditions. The pathogen was isolated from infected chilli seedlings and identified based on morphological characteristics. Aqueous extracts at 10% and 20% concentrations from seven botanicals were evaluated using the poisoned food technique, while the antagonistic potential of five fungal and two bacterial bioagents was assessed using the dual culture method. Among the botanicals, Zingiber officinale (ginger) and Allium sativum (garlic) exhibited complete inhibition (100%) of mycelial growth at both concentrations. This was followed by Curcuma longa (turmeric) and Allium cepa (onion), which showed moderate inhibitory effects. Azadirachta indica (neem) and Datura stramonium (datura) were found to be the least effective. Among the bioagents, Trichoderma harzianum (Parbhani isolate) exhibited the highest antagonistic activity with 55.03% inhibition of mycelial growth, followed by Trichoderma asperellum (52.88%) and Trichoderma harzianum (Sambhajinagar isolate) with 50.50% inhibition. The bacterial bioagents, particularly Pseudomonas fluorescens and Bacillus subtilis, showed comparatively lower inhibitory effects. The study indicates that certain botanicals and fungal biocontrol agents, especially Zingiber officinale, Allium sativum, and Trichoderma harzianum, have significant potential for the eco-friendly management of damping-off disease in chilli.